Aplicações da álgebra linear no reconhecimento facial - Silva, Naara Priscila Soares da (Universidade Federal de São Carlos, 2022)
Mathematics has been present for a long time in the daily life of society. Mathematical models are constantly constructed to explain, calculate and predict various types of phenomena. We can observe this from initial concepts, such as the four elementary operations, to advanced abstractions and calculations. Proportion of ingredients in cooking, visual language through media graphics, or calculations performed by computers with immense processing power, are examples of the application of mathematics in everyday life.Although we have the constant presence of mathematics in our lives, many still question about the application of some concepts that are studied. After all, who has never heard the famous question that every student has asked: “where am I going to use this?". In this direction, the present work will deal with concepts of eigenvectors and eigenvalues, seen during the discipline of Linear Algebra and their application in a technological tool, facial recognition.
Applications of linear algebra in facial recognition.
Keywords: Álgebra linear; Reconhecimento; Autoface; Matriz de covariância; CIENCIAS EXATAS E DA TERRA::MATEMATICA::MATEMATICA APLICADA; 4. Educação de Qualidade